Sarcopenia: The Prevalence and Associated Factors in Community-Dwelling Elderly - Sumandar Sumandar; Mersi Ekaputri; Arya Ramadia (Media Kesehatan Masyarakat Indonesia, 2023)
Sarcopenia is a syndrome characterized by a decrease in skeletal muscle mass and function due to aging. This study aims to assess the prevalence and associated factors of sarcopenia among the elderly in the Pekanbaru. 275 samples were selected using cluster sampling technique. The independent variables were socio-demographic characteristics, metabolic syndrome, independence level, physical activity, quality of life, depression, and nutritional status. Meanwhile, the dependent variable was sarcopenia. Data analysis was carried out through SPSS using statistical tests including descriptive statistics, chi-square, and multivariate logistic regression. The results show that 45.5% of the participants experienced sarcopenia. The mean age of participants was 63.3 years old; most were female; 90.2% were married; and 39.3% had moderate quality of life. The education level was mostly high school; 69.1% were not working; 72% did not experience metabolic syndrome; and 78.5% had normal nutritional status. Gender, education, metabolic syndrome, independence level, physical activity, quality of life, nutrition, marital, depression, and occupational status are associated with sarcopenia. The most significant variables for sarcopenia in the elderly were nutritional status (p=0.031) and physical activity (p= 0.016). Nutritional status and physical activity were predictors of sarcopenia. Posyandu, or integrated service post, for the elderly in the public health center, needs to be optimized which requires continuous collaboration among the doctors, nurses, nutritionists, social workers, physiotherapists, psychologists, families, religious institutions, and community shops. Furthermore, a treatment program needs to be developed, both in the community and in the health services area.